Coloration with nanoparticles: Scope for developing simultaneous colouring and functional properties onto textile surfaces—a short review. (22nd June 2022) - Kundu, Chanchal Kumar; Hossen, Md. Tanvir; Saha, Rajib
Abstract: Traditional textile dyeing using synthetic organic dyes is a hazardous method and requires the appropriate treatment of wastewater (i.e., effluent) after the dyeing process. Over time, numerous more environmentally‐friendly dyeing techniques have been innovated as a counter dyeing technique against this traditional dyeing method. Among them, nano‐coloration technology is a revolutionary innovation where textile dyeing can be carried out using solely some typical nanoparticles rather than using an organic dye, which is relatively more sustainable and green, compared to the traditional method. To date, several novel nanoparticles have been considered for a varied class of textiles and they have shown great potential in developing colour and numerous functional properties, namely antimicrobial, hydrophilic, self‐cleaning, ultraviolet (UV) protection, flame retardance and so on. Here, in this review, the recent advances regarding the uses of these nanoparticles as a novel class of colourants for the textile substrates are discussed while their related challenges and future opportunities are also analysed.